Twilight zones : subjectivity, gender, and feminism in three 21st century popular vampire romance narratives - Bridgeman, Mary (Trinity College (Dublin, Ireland). School of English, 2016)
This thesis examines three century American vampire romance narratives: the Twilight novels (2005-2008) by Stephenie Meyer and their film adaptations (2008-2012), the HBO television adaptation of Charlaine Harris' Southern Vampire Mysteries (2001-2013) True Blood (2008-2014), and the CW television adaptation (2009-) of LJ. Smith's The Vampire Diaries (1991-). Situated in the field of feminist popular cultural studies, the thesis considers the production and reception contexts, genre, and narrative texts that make up the three series. The theoretical framework used positions popular phenomena such as Twilight as culturally “symptomatic.” As such, they may be read as revealing larger cultural issues and anxieties. The methodology employed involves consideration of the public reception and popular discussion of the texts, a discussion of genre, and textual analysis of the three narratives in which selected scenes and storylines are used to illustrate the texts' overarching construction of subjectivity. Employing a range of feminist and psychoanalytic theories, this reading of the phenomenon of Twilight and related texts reveals cultural aporia around gender, feminism, and subjectivity.
Keywords: English, Ph.D.; PhD Trinity College Dublin, 2016